Analisa Kecacatan Produk Air Minum Dalam Kemasan (AMDK) dengan Metode DMAIC di PT. Amanah Insanillahia - Puji, Ari Andriyas; Sungkar, Fariz; Ulum, Panji; Haritz, Dimas; Prakoso, Indro (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
PT Amanah Insanillahia is a Bottled Drinking Water (AMDK) company that has been operating for a long time and prioritizes quality as a company strategy. There are various criteria for problems faced by the company, including quality problems in the production of drinking water in 240 ml bottles. Six sigma can be defined as a methodology that provides tools to reduce process variations and improve product quality using the DMAIC (Define, Measure, Analyze, Improve, Control) method. The purpose of this research is to determine the company's current sigma level and provide suggestions for improvements that suit the company. From the research results it can be concluded that there are 3 potential CTQs, namely imperfect cup, lack of water and machine pinching, with an average (CL) defect of 0.320, and an average DPMO of 106,476. The sigma level value is 2,77. Then the next stage is carried out by analyzing the causes of the cup not meeting standards, lack of water and being pinched by the machine. It is known that defect factors come from machine, material, method and human factors.